Identifikasi Pola Spasial dan Temporal Daerah Potensi Kebakaran Hutan di Kota Singkawang Berbasis Sistem Informasi Geografis - Muhammad Zaky Arkananta; Yahya Darmawan (Universitas Budi Luhur, 2024)
Singkawang City is one of the cities recorded as having experienced a relatively high impact of forest fires over the last 5 years. Although most forest fires are caused by natural factors, there are also impacts caused by human intervention as a serious trigger in increasing the frequency and intensity of forest fires in Singkawang City. This research aims to analyze the distribution pattern of areas prone to forest and land fires spatially and temporally in Singkawang City in 2018 - 2022 using a scoring and overlay method based on Geographic Information Systems (GIS). Some of the variables used in this research include rainfall, altitude, vegetation cover, and soil type. After the data processing process, it was continued with validation with fire point data in Singkawang City. Data analysis shows that there is significant variability in the number of hotspots from year to year, with the highest peak occurring in 2019. The results of this research show that the hotspots that occur are in accordance with the mapping of areas prone to forest fires. There is a positive correlation between the number of fire hotspots and the processing of areas prone to forest fires using scoring and overlay methods.